Wave-absorbing photo-thermal deicing integrated carbon aerogel and preparation method thereof
By co-designing and fabricating a bio-based framework with MXene, the problems of functional fragmentation and uneven loading of aerogel materials have been solved, achieving a synergistic effect of efficient wave absorption and rapid photothermal de-icing, which is suitable for extreme environment protection of aerospace and wind power equipment.
Patent Information
- Application Number
- CN202511677776.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-17
- Publication Date
- 2025-12-26
AI Technical Summary
Existing aerogel materials cannot achieve the synergistic integration of photothermal de-icing and wave absorption functions, resulting in functional fragmentation, uneven loading of photothermal materials, and insufficient wave absorption intensity, making it difficult to meet the multifunctional requirements in extreme environments.
By employing a synergistic design of a bio-based framework and MXene, a porous structure is formed through unidirectional cryo-sizing and high-temperature carbonization during the preparation process. Furthermore, a vacuum impregnation process is used to uniformly load MXene, achieving a synergistic effect between the nitrogen-doped carbon framework and cobalt species, thus forming a carbon framework-MXene conductive network.
It achieves high-efficiency wave absorption performance with X-band reflection loss of less than -40dB and rapid photothermal response with surface temperature rising to 40℃ within 30s at -30℃, and de-icing time of less than 45s, making it suitable for extreme environment protection of aerospace and wind power equipment.
Smart Images

Figure CN121198178A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of multifunctional composite material technology, specifically to an integrated carbon aerogel for absorbing microwaves, photothermal de-icing, and its preparation method. Background Technology
[0002] In extreme service environments such as aerospace radomes, wind turbine blades, and power transmission and distribution equipment, the synergistic effect of electromagnetic interference and icing hazards has become a core bottleneck restricting equipment performance: electromagnetic wave reflection can lead to radar signal distortion and reduced circuit stability, while ice adhesion can cause a surge in structural load and a decrease in energy conversion efficiency. Existing material systems generally suffer from deep-seated problems such as functional fragmentation, uneven performance, and high cost, making it difficult to meet the application requirements of "lightweight, multifunctional, and highly stable".
[0003] In the field of functional integration, the limitations of single-performance materials are becoming increasingly apparent. A study published in 2025 by the team of Associate Professors He Qinchuan and Wang Yiqun from Chengdu University of Technology in "ACSSustainableChem.Eng." showed that although CoFe-doped carbon aerogels prepared from eggplant achieved excellent electromagnetic absorption performance (minimum reflection loss RLmin = -65.8dB, effective bandwidth 6.32GHz), their thermal conductivity was only 0.031W / (m·K), lacking the ability to rapidly heat up with light and heat. In an environment of -30℃, they could not even achieve basic ice softening, making them completely unsuitable for scenarios requiring de-icing, such as wind turbine blades in high-latitude regions. In 2025, Professor Wang Yong's team at Southwest Jiaotong University reported a ZIF-derived hierarchical carbon network material in *Carbon*. Through a hierarchical porous structure design, this material achieved a photothermal conversion efficiency of up to 93.65%, and could heat up to 60°C after 1 minute of 1 sun illumination at -25°C. However, this material focuses on phase change thermal storage applications and does not introduce any magnetic or dielectric loss components. Its X-band reflection loss is only -8.2 dB, completely lacking microwave absorption capabilities and therefore unsuitable for electromagnetically sensitive devices such as radomes. Even research attempting functional integration has significant shortcomings: Patent CN202310113540.X, published by Beijing Institute of Petrochemical Technology in 2024, proposed a method for preparing MXene supported on popcorn carbon aerogel. While this method achieved improved photothermal performance (seawater evaporation rate reaching 1.8 kg·m³), it also revealed limitations. -2 However, the dense porous structure adopted in pursuit of evaporation efficiency resulted in an excessively short absorption path, with a minimum RL value of only -15.3dB. Furthermore, it did not involve optimization of de-icing performance and was essentially a localized improvement of a single-function material.
[0004] The uniformity of dispersion in photothermal materials is another key bottleneck restricting performance. Two-dimensional / one-dimensional materials such as MXene and carbon nanotubes, due to their extremely high surface energy, are prone to aggregation, leading to significant performance fluctuations. In the MXene-based hydrogel preparation method disclosed in patent CN202211078057.4, MXene is directly mixed with a polymer solution. Electron microscopy characterization shows that the size of the lamellar aggregates reaches 200–500 nm, resulting in a photothermal temperature distribution deviation exceeding ±8℃, with localized overheating and low-temperature regions coexisting, and melting time fluctuations exceeding 30 seconds. Beijing Aerospace Kain Chemical Technology Co., Ltd. attempted to modify carbon nanotubes with an aminosilane coupling agent in its patent. Although this improved the dispersion in the nylon matrix, the modification process requires the use of an ethanol-water solution system and a composite surfactant, making the steps cumbersome. Furthermore, the introduced organic components easily generate impurities during high-temperature carbonization, leading to a 15%–20% decrease in microwave absorption performance. The winter melon-based Ti3C2T published in *Desalination* in 2024... x Further research on carbon aerogels has confirmed that even when photothermal materials are loaded using a dip-coating process, there is still a "shell effect" where the sheets are enriched at the pore inlet and the interior is empty, which reduces the photothermal conversion efficiency of the material from the theoretical 90% to the actual 65%.
[0005] Optimizing the performance of bio-based scaffolds also faces many challenges. Aerogels prepared from single biomass raw materials have inherent defects: although starch-based aerogels are widely available, patent CN202311312529.2 points out that their mechanical strength is only 0.3 MPa, and their hydroxyl-rich structure easily adsorbs moisture, with a pore collapse rate of 35% at a relative humidity of 60%, which seriously affects microwave absorption and thermal conductivity stability; pure chitosan-derived carbon aerogels suffer from severe impedance mismatch due to their excessively high dielectric constant (ε'>30). Research by Deng Hongbing's team at Wuhan University shows that their effective microwave absorption bandwidth is only 2.1 GHz, which cannot cover the entire X-band. To improve performance, some studies have introduced MOF materials for modification, such as the NiCo-MOF / MXene-CNF composite aerogel disclosed in patent CN202410640856.1. Although this increases the compressive strength to 1.0 MPa and the minimum RL value to -58 dB, the cost of MOF raw materials is 5 to 8 times that of cobalt salts, and the synthesis process requires the use of toxic solvents such as DMF. Furthermore, residual metal oxide impurities after carbonization can reduce photothermal conversion efficiency, making large-scale application difficult. In addition, the carbonization volume shrinkage rate of existing bio-based aerogels generally exceeds 40%, leading to pore structure destruction and further exacerbating the instability of microwave absorption and photothermal performance.
[0006] In summary, existing aerogel materials cannot meet the integrated requirements of "photothermal de-icing—effective wave absorption—lightweighting," with the core bottlenecks being: ① unreasonable functional integration methods; ② difficulty in loading photothermal materials; and ③ insufficient performance. Therefore, developing a photothermal de-icing-wave absorption material based on low-cost processes, a three-dimensional gradient pore structure, and multifunctional synergy has significant engineering value for promoting the upgrading of materials for extreme environment protection. Summary of the Invention
[0007] To overcome the shortcomings of existing technologies, this invention provides an integrated carbon aerogel for microwave absorption, photothermal de-icing, and its preparation method. Through the synergistic design of a bio-based framework and MXene, it solves the problems of functional fragmentation, uneven loading of photothermal materials, and insufficient microwave absorption intensity in existing materials, achieving a synergistic integration of photothermal de-icing and microwave absorption functions. It is suitable for extreme environmental protection scenarios such as aerospace and wind power equipment.
[0008] To achieve the above objectives, an integrated carbon aerogel for absorbing microwaves, photothermal heating, and de-icing is designed, characterized by comprising the following raw materials: dominant bio-based material: 5-15 parts; auxiliary bio-based material: 3-10 parts; cobalt salt: 0.5-3 parts; photothermal material: 1-5 parts; MXene material; dispersion medium: 40-80 ml of 1% v / v acetic acid solution; photothermal material dispersion: concentration of 0.5-2 mg / mL, 30-60 ml.
[0009] The dominant bio-based material is chitosan, with a degree of deacetylation ≥85%.
[0010] The auxiliary bio-based material is one or more combinations of glucose, starch, sodium alginate, and cellulose.
[0011] The MXene material mentioned is not limited to one or a combination of sheet-like MXene, graphene, and carbon nanotubes.
[0012] The MXene material is an exfoliated nanosheet with a sheet size of 1–5 μm.
[0013] The cobalt salt is selected from one or a combination of several of CoCl2·6H2O, Co(NO3)2·6H2O, and CoSO4·7H2O.
[0014] A method for preparing an integrated microwave absorption, photothermal de-icing carbon aerogel, characterized by comprising the following steps:
[0015] Step 1, preparation of hydrogel precursor: Dissolve cobalt salt completely in 1% v / v acetic acid solution and stir at 30-40℃ for 10-20 min until a transparent solution is formed; add chitosan powder in proportion and stir at 35-40℃ for 1-2 h until completely swollen; then add auxiliary bio-based material and continue stirring for 30-60 min to form a uniform and viscous bio-based cobalt salt hydrogel precursor;
[0016] Step 2, unidirectional cryo-sizing: Pour the hydrogel precursor into a self-made hollow Teflon mold, and fix the bottom of the mold to a copper plate; place it in a low temperature environment of -25 to -35℃ and freeze it unidirectionally from bottom to top for 24 hours to allow ice crystals to grow in the vertical direction;
[0017] Step 3, vacuum freeze drying: The frozen precursor is transferred to a vacuum freeze dryer and freeze-dried for 36 to 48 hours at a temperature of -50 to -40°C and a vacuum degree of <10Pa to remove ice crystals and obtain an ultralight cobalt-doped bio-based aerogel precursor.
[0018] Step 4, high-temperature carbonization: The freeze-dried precursor is placed in a tube furnace, nitrogen gas is introduced, and the temperature is raised to 600-800℃ at a heating rate of 5℃ / min, and held for 2-3 hours; it is then naturally cooled to room temperature to obtain nitrogen-doped cobalt-modified carbon aerogel, labeled as CoNC.
[0019] Step 5, Impregnation and adsorption of photothermal materials: Disperse MXene material in deionized water and sonicate for 30-60 min to prepare a uniform dispersion of 0.5-2 mg / mL; immerse the carbonized CoNC in the dispersion and vacuum-assisted adsorption for 1-3 h to uniformly load MXene material into the porous structure of the carbonized CoNC; vacuum dry at 40-60℃ for 2-4 h to obtain an integrated carbon aerogel for absorbing light, photothermal and de-icing, labeled as CoNC@M.
[0020] In step 4, the carbonization temperature is preferably 700℃. At this temperature, the nitrogen-doped carbon framework and cobalt species formed by chitosan carbonization are evenly distributed, and the synergistic effect with the subsequently loaded MXene is optimal.
[0021] In step 5, the weight ratio of MXene material to carbonized carbon aerogel is 0.1 to 0.3:1, and the ultrasonic power of the MXene dispersion is 300 to 500 W.
[0022] The performance indicators of CoNC@M are a density of 45-55 mg / cm³. 3 The minimum X-band reflection loss RL under 8-12GHz conditions is <-40dB; the effective absorption bandwidth under RL <-10dB conditions is >4GHz; the surface temperature is ≥40℃ within 1 sun illumination for 30s at -30℃, and the melting time of a 3mm thick ice layer is <45s.
[0023] Compared with the prior art, this invention provides an integrated carbon aerogel for microwave absorption, photothermal de-icing and its preparation method. Through the synergistic design of bio-based framework and MXene, it solves the problems of functional fragmentation of existing materials, uneven loading of photothermal materials and insufficient microwave absorption intensity, and achieves synergistic integration of photothermal de-icing and microwave absorption functions. It is suitable for extreme environment protection scenarios such as aerospace and wind power equipment. Attached Figure Description
[0024] Figure 1 This is a transmission electron microscope image of the cross-section of the sample from this invention.
[0025] Figure 2 This is a waveform absorption performance diagram of the sample from this invention. Detailed Implementation
[0026] The present invention will now be further described with reference to the accompanying drawings.
[0027] like Figure 1 , Figure 2 As shown, an integrated carbon aerogel for absorbing microwaves, photothermal de-icing includes the following raw materials: main bio-based material: 5-15 parts; auxiliary bio-based material: 3-10 parts; cobalt salt: 0.5-3 parts; photothermal material: 1-5 parts; MXene material; dispersion medium: 40-80 ml of 1% v / v acetic acid solution; photothermal material dispersion: 30-60 ml with a concentration of 0.5-2 mg / mL.
[0028] The dominant bio-based material is chitosan, with a degree of deacetylation ≥85%.
[0029] The auxiliary bio-based material is one or more combinations of glucose, starch, sodium alginate, and cellulose.
[0030] MXene materials, but not limited to one or a combination of sheet-like MXene, graphene, and carbon nanotubes.
[0031] MXene material is exfoliated nanosheets with a sheet size of 1–5 μm.
[0032] The cobalt salt is selected from one or a combination of several of CoCl2·6H2O, Co(NO3)2·6H2O, and CoSO4·7H2O.
[0033] A method for preparing an integrated carbon aerogel for microwave absorption, photothermal de-icing includes the following steps:
[0034] Step 1, preparation of hydrogel precursor: Dissolve cobalt salt completely in 1% v / v acetic acid solution and stir at 30-40℃ for 10-20 min until a transparent solution is formed; add chitosan powder in proportion and stir at 35-40℃ for 1-2 h until completely swollen; then add auxiliary bio-based material and continue stirring for 30-60 min to form a uniform and viscous bio-based cobalt salt hydrogel precursor;
[0035] Step 2, unidirectional cryo-sizing: Pour the hydrogel precursor into a self-made hollow Teflon mold, and fix the bottom of the mold to a copper plate; place it in a low temperature environment of -25 to -35℃ and freeze it unidirectionally from bottom to top for 24 hours to allow ice crystals to grow in the vertical direction;
[0036] Step 3, vacuum freeze drying: The frozen precursor is transferred to a vacuum freeze dryer and freeze-dried for 36 to 48 hours at a temperature of -50 to -40°C and a vacuum degree of <10Pa to remove ice crystals and obtain an ultralight cobalt-doped bio-based aerogel precursor.
[0037] Step 4, high-temperature carbonization: The freeze-dried precursor is placed in a tube furnace, nitrogen gas is introduced, and the temperature is raised to 600-800℃ at a heating rate of 5℃ / min, and held for 2-3 hours; it is then naturally cooled to room temperature to obtain nitrogen-doped cobalt-modified carbon aerogel, labeled as CoNC.
[0038] Step 5, Impregnation and adsorption of photothermal materials: Disperse MXene material in deionized water and sonicate for 30-60 min to prepare a uniform dispersion of 0.5-2 mg / mL; immerse the carbonized CoNC in the dispersion and vacuum-assisted adsorption for 1-3 h to uniformly load MXene material into the porous structure of the carbonized CoNC; vacuum dry at 40-60℃ for 2-4 h to obtain an integrated carbon aerogel for absorbing light, photothermal and de-icing, labeled as CoNC@M.
[0039] In step 4, the carbonization temperature is preferably 700℃. At this temperature, the nitrogen-doped carbon framework and cobalt species formed by chitosan carbonization are evenly distributed, and the synergistic effect with the subsequently loaded MXene is optimal.
[0040] In step 5, the weight ratio of MXene material to carbonized carbon aerogel is 0.1 to 0.3:1, and the ultrasonic power of the MXene dispersion is 300 to 500 W.
[0041] The performance indicators of CoNC@M are a density of 45-55 mg / cm³. 3 The minimum X-band reflection loss RL under 8-12GHz conditions is <-40dB; the effective absorption bandwidth under RL <-10dB conditions is >4GHz; the surface temperature is ≥40℃ within 1 sun illumination for 30s at -30℃, and the melting time of a 3mm thick ice layer is <45s.
[0042] The porous structure of carbon aerogel is "vertically oriented micron pores (10-50 μm) + pore wall nanopores (50-200 nm)". MXene is uniformly adsorbed on the pore wall surface to form a "carbon skeleton-MXene" conductive network, which not only enhances the photothermal conversion efficiency (≥90%), but also improves the microwave absorption performance through the synergistic effect of dielectric loss and magnetic loss.
[0043] Example 1 (Preferred process: chitosan + glucose + MXene)
[0044] Raw material ratio: 10 parts chitosan, 5 parts glucose, 1.5 parts CoCl2·6H2O, Ti3C2T x Two portions of MXene; 60 ml of 1% v / v acetic acid solution, and 40 ml of MXene dispersion (1 mg / mL);
[0045] Preparation of hydrogel precursor: 1.5g CoCl2·6H2O was dissolved in 60ml acetic acid solution and stirred at 35℃ for 15min; 10g chitosan was added and stirred at 35℃ for 1.5h until swollen; 5g glucose was added and stirring was continued for 45min to form a viscous gel.
[0046] One-way freezing and lyophilization: The gel was poured into a mold (bottom copper plate) and frozen at -30℃ for 72h; then lyophilized at -45℃ and 5Pa vacuum for 75h to obtain the precursor.
[0047] High-temperature carbonization: Nitrogen gas was passed through a tube furnace (80 mL / min), the temperature was increased to 700℃ at 5℃ / min, held for 2.5 h, and then cooled to obtain CoNC-700;
[0048] Impregnation and adsorption: 2g Ti3C2T x Add 40 ml of deionized water and sonicate at 400 W for 45 min to obtain a dispersion; immerse CoNC-700 in the dispersion, adsorb under vacuum at 10 Pa for 2 h, and dry under vacuum at 70 °C for 3 h to obtain CoNC-700@MXene.
[0049] Example 2 (Auxiliary material replacement: chitosan + sodium alginate + MXene)
[0050] Raw material ratio: 12 parts chitosan, 4 parts sodium alginate, 1.8 parts Co(NO3)2·6H2O, Ti2CT x MXene 2.5 parts; 1% v / v acetic acid solution 70 ml; MXene dispersion (1.5 mg / mL) 50 ml;
[0051] Hydrogel preparation: Co(NO3)2·6H2O was dissolved in acetic acid solution and stirred at 38℃ for 20 min; chitosan and sodium alginate were added and stirred at 38℃ for 2 h.
[0052] Subsequent steps: same as in Example 1, including freezing, freeze-drying, carbonization (750°C), and impregnation adsorption;
[0053] Example 3 (Photothermal material replacement: chitosan + glucose + graphene)
[0054] Raw material ratio: 10 parts chitosan, 5 parts glucose, 1.5 parts CoCl2·6H2O, 2 parts graphene; 60 ml 1% v / v acetic acid solution, 40 ml graphene dispersion (1 mg / mL);
[0055] Subsequent steps: Same as in Example 1, except that MXene is replaced with graphene;
[0056] Comparative Example 1 (No MXene Load)
[0057] Consistent with Example 1, only the impregnation and adsorption in step 5 were removed;
[0058] Comparative Example 2 (MXene physical mixing rather than impregnation)
[0059] Consistent with Example 1, except that MXene was added in step 1 (step 5 was not performed).
[0060] The performance test results are shown in Table 1 below.
[0061] Table 1
[0062] Testing items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 <![CDATA[Density (mg / cm 3 )]]> 48.6 50.5 49.8 47.5 48.1 Minimum RL value in X-band (dB) -42.3 -40.5 -38.2 -41.8 -41.6 Effective bandwidth (GHz) 4.2 4.0 4.0 4.2s 4.1 Temperature rises by 30°C after 30 seconds of exposure to light (°C) 52 48 45 / / Melting time of 3mm ice layer (s) 38 42 44 / /
[0063] In summary, the structural design of this invention dominates the upper limit of performance while taking into account both de-icing efficiency and wave absorption performance. The aperture gradient can be flexibly adjusted according to application requirements (such as wind power equipment requiring rapid de-icing and radar domes requiring efficient wave absorption), reflecting the flexibility of the structural design. Moreover, it achieves a reasonable and efficient synergistic integration of photothermal de-icing and efficient wave absorption, providing a promising solution for the development of functional materials for extreme environments.
[0064] The objective of this invention is achieved through the following technical solution:
[0065] (1) The raw material system is designed with a bio-based framework as the main component, with chitosan as the core raw material. The amino groups in its molecular chain form active sites such as pyridine nitrogen and pyrrole nitrogen after carbonization, which not only provide dielectric loss centers for microwave absorption, but also enhance the adsorption capacity for MXene. Auxiliary bio-based materials such as glucose are used to adjust the gel viscosity and promote the uniform formation of oriented pores. Starch / sodium alginate enhances the mechanical stability of the gel and avoids structural collapse during freezing, thus broadening the selection range of bio-based raw materials. Cobalt salt is doped and forms Co after high-temperature carbonization. o Species such as Co-N4 are introduced to improve magnetic and dielectric loss absorption performance in synergy; the photothermal material is mainly MXene (preferably Ti3C2T). xIts layered structure has a high specific surface area and surface plasmon resonance effect, with a photothermal conversion efficiency of ≥90%. At the same time, its excellent conductivity can enhance the dielectric loss of the carbon skeleton. Graphene and carbon nanotubes are alternatives to assist in the construction of conductive networks.
[0066] (2) The core preparation process employs unidirectional freezing and freeze-drying. Utilizing the thermal conductivity difference of the copper plate, ice crystals grow vertically, forming directional micron-sized channels (10–50 μm). This extends the electromagnetic wave reflection path (enhancing absorption) and provides a channel for uniform loading of MXene. Vacuum freeze-drying preserves the pore structure, ensuring low density. High-temperature carbonization occurs at 600–800℃ under a nitrogen atmosphere, causing chitosan to deacetylate and form a nitrogen-doped carbon framework, while cobalt salt is converted to Co. o The / Co-N4 structure avoids high-temperature oxidation caused by premature introduction of MXene. Vacuum impregnation adsorption allows carbonized carbon aerogel to be immersed in an MXene dispersion. Under vacuum conditions, air inside the pores is removed, allowing MXene to bind to the nitrogen sites of the carbon framework through hydrogen bonds, resulting in uniform loading on the pore walls and solving the aggregation problem caused by physical mixing.
[0067] (3) The functional synergy mechanism is first reflected in efficient absorption. Nitrogen-doped carbon skeleton provides dielectric loss, cobalt species provides magnetic loss, and the high conductivity of MXene enhances interface polarization and conduction loss. The three work together to make the minimum RL value of X band < -40dB; the directional channel extends the electromagnetic wave propagation path and the effective absorption bandwidth > 4GHz; secondly, rapid photothermal de-icing. Under illumination, Xene efficiently converts light energy into heat energy through surface plasma effect. The directional channel serves as a heat conduction channel to make the heat evenly distributed. Cobalt doping further enhances the thermal conductivity of carbon skeleton.
[0068] This invention has the following significant advantages:
[0069] (1) Breakthrough in Functional Synergy: Achieving Integrated Wave Absorption and Photothermal De-icing. This invention abandons the existing design concept of "functional separation" and solves the problems of electromagnetic interference and icing simultaneously through a ternary synergistic system of "nitrogen-doped carbon framework-cobalt species-MXene". While maintaining the minimum RL value in the X-band < -40dB, this invention achieves a rapid photothermal response of heating from -30℃ to 40-55℃ in 30s under light irradiation.
[0070] (2) Load uniformity optimization: To overcome the problem of agglomeration of photothermal materials, an innovative "high-temperature carbonization followed by vacuum impregnation" process was adopted. The pyridine nitrogen and pyrrole nitrogen sites formed by the carbonization of chitosan form hydrogen bonds with the MXene sheets. Combined with the vacuum environment to remove air from the pores, the MXene is effectively loaded.
[0071] (3) Upgraded Framework Performance: A composite framework design balancing environmental friendliness with electromagnetic and mechanical properties, primarily based on chitosan and supplemented by multiple bio-based materials, solves the impedance mismatch and volume shrinkage problems of pure chitosan-based materials. This is achieved by introducing Co salts... o The / Co-N4 magnetic loss component, combined with the dielectric enhancement effect of MXene, makes the impedance matching factor of the material close to 1, effectively absorbing waves.
Claims
1. A carbon aerogel integrating microwave absorption, photothermal de-icing, and de-icing, characterized in that, The raw materials include: 5-15 parts of the main bio-based material; and 3-10 parts of the auxiliary bio-based material. Cobalt salt: 0.5–3 parts; Photothermal material: 1–5 parts, MXene material; Dispersion medium: 1% v / v acetic acid solution 40–80 ml; Photothermal material dispersion: concentration 0.5–2 mg / mL, 30–60 ml.
2. The integrated carbon aerogel for microwave absorption, photothermal de-icing according to claim 1, characterized in that: The dominant bio-based material is chitosan, with a degree of deacetylation ≥85%.
3. The integrated carbon aerogel for microwave absorption, photothermal de-icing according to claim 1, characterized in that: The auxiliary bio-based material is one or more combinations of glucose, starch, sodium alginate, and cellulose.
4. The integrated carbon aerogel for microwave absorption, photothermal de-icing according to claim 1, characterized in that: The MXene material mentioned is not limited to one or a combination of sheet-like MXene, graphene, and carbon nanotubes.
5. The integrated carbon aerogel for microwave absorption, photothermal de-icing according to claim 1 or 4, characterized in that: The MXene material is an exfoliated nanosheet with a sheet size of 1–5 μm.
6. The integrated carbon aerogel for microwave absorption, photothermal de-icing according to claim 1, characterized in that: The cobalt salt is selected from one or a combination of several of CoCl2·6H2O, Co(NO3)2·6H2O, and CoSO4·7H2O.
7. A method for preparing an integrated carbon aerogel for microwave absorption, photothermal de-icing, and de-icing, characterized in that, Includes the following steps: Step 1, preparation of hydrogel precursor: Dissolve cobalt salt completely in 1% v / v acetic acid solution and stir at 30-40℃ for 10-20 min until a transparent solution is formed; add chitosan powder in proportion and stir at 35-40℃ for 1-2 h until completely swollen; then add auxiliary bio-based material and continue stirring for 30-60 min to form a uniform and viscous bio-based cobalt salt hydrogel precursor; Step 2, unidirectional cryo-sizing: Pour the hydrogel precursor into a self-made hollow Teflon mold, and fix the bottom of the mold to a copper plate; place it in a low temperature environment of -25 to -35℃ and freeze it unidirectionally from bottom to top for 24 hours to allow ice crystals to grow in the vertical direction; Step 3, vacuum freeze drying: The frozen precursor is transferred to a vacuum freeze dryer and freeze-dried for 36 to 48 hours at a temperature of -50 to -40°C and a vacuum degree of <10Pa to remove ice crystals and obtain an ultralight cobalt-doped bio-based aerogel precursor. Step 4, high-temperature carbonization: The freeze-dried precursor is placed in a tube furnace, nitrogen gas is introduced, and the temperature is raised to 600-800℃ at a heating rate of 5℃ / min, and held for 2-3 hours; it is then naturally cooled to room temperature to obtain nitrogen-doped cobalt-modified carbon aerogel, labeled as CoNC. Step 5, Impregnation and adsorption of photothermal materials: Disperse MXene material in deionized water and sonicate for 30-60 min to prepare a uniform dispersion of 0.5-2 mg / mL; immerse the carbonized CoNC in the dispersion and vacuum-assisted adsorption for 1-3 h to uniformly load MXene material into the porous structure of the carbonized CoNC. Vacuum drying at 40–60℃ for 2–4 hours yielded an integrated carbon aerogel for microwave absorption, photothermal de-icing, and de-icing, labeled CoNC@M.
8. The preparation method of the integrated carbon aerogel for microwave absorption, photothermal de-icing according to claim 7, characterized in that: In step 4, the carbonization temperature is preferably 700℃. At this temperature, the nitrogen-doped carbon framework and cobalt species formed by chitosan carbonization are evenly distributed, and the synergistic effect with the subsequently loaded MXene is optimal.
9. The preparation method of the integrated microwave absorption, photothermal de-icing carbon aerogel according to claim 7, characterized in that: In step 5, the weight ratio of MXene material to carbonized carbon aerogel is 0.1 to 0.3:1, and the ultrasonic power of the MXene dispersion is 300 to 500 W.
10. The method for preparing an integrated carbon aerogel for microwave absorption, photothermal de-icing according to claim 7, characterized in that: The performance indicators of CoNC@M are a density of 45-55 mg / cm³. 3 The minimum X-band reflection loss RL under 8-12GHz conditions is <-40dB; the effective absorption bandwidth under RL <-10dB conditions is >4GHz; the surface temperature is ≥40℃ within 1 sun illumination for 30s at -30℃, and the melting time of a 3mm thick ice layer is <45s.
Citation Information
Patent Citations
MXene-based hydrogel material with directional pore structure as well as preparation method and application of MXene-based hydrogel material
CN115651219A
Aerogel thermal insulation material and method for producing the same
CN117362742B
Carbon aerogel / MXene composite material as well as preparation method and application thereof
CN118405748A
High-toughness puncture-resistant ultrathin composite hydrogel and preparation method thereof
CN118562156A
Preparation method of glucose crosslinked composite gel and application of glucose crosslinked composite gel to cigarettes
CN107556499A
Cited By
Biphase hybrid anti-icing coating as well as preparation method and application thereof
CN121975431A